DreamScape - Christian, Kezia Agatha (Nanyang Technological University, 2020)
DreamScape is an isometric PC Game Demo made by three ADM Students. Made with Unreal Engine, it's a game with a fresh mechanic concept derived from the existing hack-and-slash genre. The story revolves around a 6 year old girl named Tuffy, that is trapped in a dream world, and her journey to escape from it.